Haematological Alterations In Bitches Affected With Pyometra - Gupta , A.K.; Dhami , A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Haematological parameters were evaluated in nine pyometric and eight healthy bitches before and after ovario-hysterectomy. Significantly lower pre-operative mean haemoglobin (Hb) and total erythrocyte count (TEC) was found in pyometric bitches (11.22±0.83 g % and 5.76± 0.33 million/ cmm) than in healthy bitches (14.90±0.34 g % and 7.80±0.18 million/cmm). The mean pre-operative PCV value was significantly (P
Keywords: Bitch; pyometra; haematology; ovario-hysterectomy